Iodixanol density gradients as an effective phytoplasma enrichment approach to improve genome sequencing - Rodrigues Jardim, Bianca; Tran-Nguyen, Lucy T. T.; Gambley, Cherie; Rodoni, Brendan; Constable, Fiona E. (Frontiers in Microbiology, 2022)
Obtaining complete phytoplasma genomes is difficult due to the lack of a culture system for these bacteria. To improve genome assembly, a non-ionic, low- and iso-osmotic iodixanol (Optiprep™) density gradient centrifugation method was developed to enrich for phytoplasma cells and deplete plant host tissues prior to DNA extraction and high throughput sequencing (HTS). After density gradient enrichment, potato infected with a ‘Candidatus Phytoplasma australasia’-related strain showed a ~14-fold increase in phytoplasma HTS reads, with a ~1.7-fold decrease in host genomic reads compared to DNA extracted from the same sample without density gradient centrifugation enrichment. Additionally, phytoplasma genome assemblies from libraries equalised to 5 million reads were, on average, ~15,000 bp larger and more contiguous (N50 ~14,800 bp larger) than assemblies from DNA extracted from the infected potato without enrichment. The method was repeated on capsicum infected with Sweet Potato Little Leaf phytoplasma (‘Ca. Phytoplasma australasia’-related strain)with a lower phytoplasma titre than the potato. In capsicum, ~3-fold more phytoplasma reads and ~2-fold less host genomic reads were obtained, with the genome assembly size and N50 values from libraries equalised to 3.4 million reads ~137,000 bp and ~4,000 bp larger, respectively, compared to DNA extracted from infected capsicum without enrichment. Phytoplasmas from potato and capsicum were both enriched at a density of 1.049 – 1.058 g/mL. Finally, we present two highly contiguous ‘Ca. Phytoplasma australasia’ phytoplasma reference genomes sequenced from naturally infected Solanaceae hosts in Australia. Obtaining high quality phytoplasma genomes from naturally infected hosts will improve insights into phytoplasma taxonomy, which will improve detection and disease management.